Raising Dairy Herd Replacements - Fausett, Marvin R.; Langemeier, Larry N. (My University, 1997)
This publication discusses the decision making factors for raising dairy herd replacements.
MF399_1997_10
Keywords: MF399; Economics; Livestock; MF